Strength development following a six-week risk reduction athletic development training program in men and women - Cleary, C. J.; Crane, K.; Vopat, L. M.; Vopat, B. G.; Herda, A. A. (Sports Medicine and Health Science, 2024)
This study retrospectively evaluated data from an athlete management system on the impact of a 6-week, 12-session risk-reduction athletic development training program on maximal isometric strength in post-rehabilitative and healthy men and women. Maximal isometric quadriceps and hamstrings strength were evaluated bilaterally before and after the training program. Out of 55 athletes that had participated in the program, a total of 37 athletes` (13-28 years old) recorded outcomes were utilized in analyses. Thirty-one athletes had undergone rehabilitation (post-rehabilitative athletes) after orthopedic knee surgeries. Six athletes with no previous surgeries performed (healthy athletes) also completed the 6-week program. Repeated measures analyses of variance (leg x time) assessed changes in quadriceps and hamstrings strength at an alpha of p = 0.05. There was a main effect for time where the post-rehabilitative athletes` quadriceps and hamstrings strength increased by (mean difference ± standard error) (4.2 ± 0.7) kg (p < 0.01) and (4.5 ± 0.9) kg (p < 0.01) respectively, with legs [operative (OP) and non-operative (NOP)] combined. With time points combined, the OP limb was weaker than the NOP limb for quadriceps strength by (2.9 ± 0.7) kg (p < 0.01) with no differences in hamstrings strength. For the healthy athletes, there were no changes for quadriceps strength and hamstring strength improved across time by (5.3 ± 1.4) kg (p = 0.01) with legs combined.